A rabbit reticulocyte model for the role of hemin-controlled repressor in hypochromic anemias. - Freedman, M L (1976)
Hemin allows maximal protein synthesis in intact rabbit reticulocytes and their cell-free lysate preparations by retarding the formation of a translational repressor (HCR) found in the postribosomal supernate. In order to evaluate the role of HCR in the pathogenesis of hypochromic anemias, HCR was isolated and partially purified from intact rabbit reticulocytes incubated in vitro with either 0.1 mM alpha,alpha-dipyridyl (an iron-chelating agent) or 0.1 M ethanol. Both of these agents inhibit reticulocyte protein synthesis. Hemin (50 muM) protects against the inhibition by both agents. A ferrous iron-transferrin mixture, however, protects only against alpha,alpha-dipyridyl. Both alpha,alpha-dipyridyl and ethanol inhibit heme synthesis before the time that protein synthesis is affected, while neither lowers either ATP or GSH levels. These results indicate that while both agents inhibit heme synthesis, alpha,alpha-dipyridyl does so by inducing iron deficiency while ethanol works at a non-iron-requiring step. When HCR was isolated from intact cells and assayed in the reticulocyte cell-free systems, plus and minus hemin, premature appearance of HCR was found in cells incubated in vitro with alpha,alpha-dipyridyl or ethanol. When hemin was present in the intact cell incubation, the appearance of HCR was retarded. The HCR from alpha,alpha-dipyridyl ethanol-treated cells was partially purified and eluted at the same location on a Sephadex G-200 column (molecular weight approximately 3 x 10(5)) as that from postribosomal supernates incubated minus hemin. In addition rabbits with phenylhydrazine-induced hemolytic anemia were given intravenous ethanol in vivo at a dose of 0.4 ml/kg. This concentration of alcohol resulted in an inhibition of the rate of heme synthesis and protein synthesis as well as an acceleration of HCR formation in reticulocytes. The HCR from these in vivo treated rabbits was isolated, partially purified, and assayed in an identical fashion as the in vitro experiments. These in vivo experiments further support the physiological and pathophysiological role of HCR in reticulocytes. On the basis of these results a model for a role of HCR in some of the hypochromic anemias is proposed. In iron deficiency or chronic disease (where iron is not available to the erythroblast for heme synthesis) HCR appears prematurely and inhibits protein synthesis. When heme synthesis is inhibited by ethanol but there is sufficient intracellular iron, HCR appears prematurely and inhibits protein synthesis, iron accumulates in the erythroblast, and the end result is sideroblastic anemia.